Postoperative peri-axillary seroma following axillary artery cannulation for surgical treatment of acute type A aortic dissection - Katsanos Konstantinos; Baikoussis Nikolaos G; Apostolakis Efstratios E; Karanikolas Menelaos (Journal of Cardiothoracic Surgery, 2010)
Abstract The arterial cannulation site for optimal tissue perfusion and cerebral protection during cardiopulmonary bypass (CPB) for surgical treatment of acute type A aortic dissection remains controversial. Right axillary artery cannulation confers significant advantages, because it provides antegrade arterial perfusion during cardiopulmonary bypass, and allows continuous antegrade cerebral perfusion during hypothermic circulatory arrest, thereby minimizing global cerebral ischemia. However, right axillary artery cannulation has been associated with serious complications, including problems with systemic perfusion during cardiopulmonary bypass, problems with postoperative patency of the artery due to stenosis, thrombosis or dissection, and brachial plexus injury. We herein present the case of a 36-year-old Caucasian man with known Marfan syndrome and acute type A aortic dissection, who had direct right axillary artery cannulation for surgery of the ascending aorta. Postoperatively, the patient developed an axillary perigraft seroma. As this complication has, not, to our knowledge, been reported before in cardiothoracic surgery, we describe this unusual complication and discuss conservative and surgical treatment options.